Construction of Recombinant Inbred Lines and Indentification of QTL for Grain Number Traits of Gaozhou Wild Rice - Xing HUO; Yongmei YU; Shuqing QIU; Dilin LIU; Le KONG; Wuge LIU; Feng WANG (Guangdong nongye kexue)
【Objective】Wild rice (Oryza rufipogon) possesses a wealth of genetic resources. The study aims to identify quantitative trait loci (QTLs) controlling the grain number per panicle in rice by constructing recombinant inbred lines (RILs) of wild rice and performing QTL analysis. This will provide a molecular basis and genetic resources for the genetic improvement of rice.【Method】A recombinant inbred line population with wild rice ancestry was developed through crosses between Gaozhou wild rice and 'Zhonghua 11', followed by multiple generations of selfing. High-density genotyping arrays were used to genotype the population, and a high-density genetic map was constructed based on molecular marker analysis. The phenotypic data for grain number per panicle were examined for two years. QTL analysis was conducted by using QTL IciMapping software with the combination of phenotypic data and SNP marker information.【Result】A population consisting of 316 recombinant inbred lines was successfully constructed. Phenotypic observations revealed rich genetic diversity within the population and good potential for application in improving the grain number per panicle. Ten QTLs regulating the grain number per panicle in rice were detected, among which four QTLs were detected in 2022 and six QTLs were detected in 2023. The phenotypic contribution of one QTL on chromosome 11 was the highest, accounting for 13.78%. The QTL located on chromosomes 2 was stably detected in two years. The additive effect was positive for 9 out of 10 QTLs detected at 2 years.【Conclusion】The recombinant inbred line of Gaozhou wild rice was successfully constructed, which revealed the application potential of Gaozhou wild rice in improving grain number per panicle of rice. QTL analysis revealed the genetic basis controlling the grain number per panicle in rice.